Comparison of time utilization in an academic inpatient versus an outpatient vascular laboratory. Issue 9 (28th June 2016) - Oriowo, Babatunde A.; Hoffman, Kaitlin; Evans, Julie; Haurani, Mounir J.; Satiani, Bhagwan
ABSTRACT: Purpose: Efficient, cost‐effective services in vascular laboratories (VLs) will be required in tomorrow's health care environment. Inpatient VLs (IPVL) are burdened with complex patients, excessive workload, and a high percentage of bedside tests. Outpatient VLs (OPVL) are therefore presumed to be more productive and efficient. We compared time utilization in OPVLs and IPVL to test this hypothesis. Methods: Vascular sonographers at an academic IPVL and OPVL were asked to track their daily activities during five consecutive weekdays. Test type, scan time, delays in patient arrival, preparation for the test, computer entry, and administrative time (patient‐ and non‐patient‐related) were logged. Results: Delay in patient arrival and non‐patient‐related administration activities were both significantly greater in the OPVL ( p < 0.01 and 0.03, respectively). Actual scan time occupied only 38.8% of the technologist's day, with the rest spent on patient‐ and non‐patient‐related activities. Conclusions: No appreciable differences were noted between IPVL and OPVL in most of the efficiency parameters measured. General administration time and delay in patient arrival were greater in the OPVL. Thus, OPVL were not more efficient than IPVL. In order to maximize efficiency in the OPVL, non‐patient‐related activities, which occupy over a quarter of the daily workday, must be shifted from technologists to support staff. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 44 :540–544, 2016